The great Brazilian recession from an Austrian perspective: a vector autoregression (VAR) analysis - Bonkevitch, Leonardo (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2025)
The present article aims to empirically evaluate switches in the money and credit supply in Brazil from 2009 to 2015, and to determine whether such changes may lead to cyclical fluctuations, as proposed by the Austrian Business Cycle Theory (ABCT). To this end, a contextualization of the period in question is provided. To support the findings, a vector autoregressive model and Granger causality test were used to examine the variations in the money supply and its effect on the capital structure. Except for the extractive industry, all industrial ratios and aggregate industrial production correlate with variations in the money supply, as well as national output and idleness levels. Therefore, the results support the patterns suggested by the Austrian Business Cycle Theory and confirm the hypothesis of cyclical fluctuations caused by monetary shocks.